Procedures to develop a computerized adaptive test to assess patient-reported physical functioning. - McCabe, Erin; Gross, Douglas P.; Bulut, Okan (Quality of Life Research, 2018)
Purpose: The purpose of this paper is to demonstrate the procedures to develop and implement a computerized adaptive patient-reported outcome (PRO) measure using secondary analysis of a dataset and items from fixed-format legacy measures.Methods: We conducted secondary analysis of a dataset of responses from 1429 persons with work-related lower extremity impairment. We calibrated three measures of physical functioning on the same metric, based on item response theory (IRT). We evaluated efficiency and measurement precision of various computerized adaptive test (CAT) designs using computer simulations.Results: IRT and confirmatory factor analyses support combining the items from the three scales for a CAT item bank of 31 items. The item parameters for IRT were calculated using the generalized partial credit model. CAT simulations show that reducing the test length from the full 31 items to a maximum test length of 8 items, or 20 items is possible without a significant loss of information (95, 99% correlation with legacy measure scores).Conclusions: We demonstrated feasibility and efficiency of using CAT for PRO measurement of physical functioning. The procedures we outlined are straightforward, and can be applied to other PRO measures. Additionally, we have included all the information necessary to implement the CAT of physical functioning in the electronic supplementary material of this paper.